A Critical Examination of the Impact of Religious Teaching on Sexual Behaviour Among Undergraduates in Delta State of Nigeria (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
This study examines the influence of religious teaching on sexual behaviour among university students in Delta State, Nigeria. With rising concerns about premarital sex, unwanted pregnancies, sexually transmitted infections, and transactional relationships on campuses, this research investigates whether religious teachings continue to shape students' sexual conduct in contemporary university settings. The study focused on three institutions: Delta State University (DELSU), Federal University of Petroleum Resources (FUPRE), and Novena University Ogume (NUO). Using a qualitative method, data were collected through interviews with campus fellowship leaders and students, supplemented by academic literature review. Participants were selected through purposive sampling, and responses were analysed thematically, with strict adherence to ethical standards including voluntary participation, confidentiality, and anonymity. Findings reveal that religious teaching continue to influence students' moral outlook by promoting abstinence, self-discipline, and respect for relationships; however, a significant gap exists between belief and practice. Several factors undermine the effectiveness of religious guidance, including peer pressure, digital media influence, economic hardship, and inconsistent role modelling from religious leaders. Campus fellowships nonetheless serve as important spaces for moral guidance through mentorship, open discussions, and special programmes that emphasise responsible behaviour. The study concludes that while religious teachings impact students' sexual behaviour, the degree of influence varies considerably among individuals based on social and environmental factors. Recommendations include adopting more student-centred approaches, integrating technology and social media in religious education, providing economic and emotional support, and maintaining consistency in religious leadership to enhance the relevance and effectiveness of moral teachings in guiding students' sexual conduct.